Peranan Nomor Induk Berusaha (NIB) Sebagai Legalitas Usaha Bagi Pertumbuhan Bisnis UMKM Tape Semen Bu Suwarti - Audy Herlina Puspitasari; Condro Widodo (MENGABDI : Jurnal Hasil Kegiatan Bersama Masyarakat, 2024)
A country's economic growth can increase because of the important role of Micro, Small and Medium Enterprises (MSMEs). Micro, Small and Medium Enterprises (MSMEs) are productive economic enterprises that were born as one of human activities to fulfill their daily needs. This research discusses the role of the Business Identification Number (NIB) in the context of business legality to support the business growth of Micro, Small and Medium Enterprises (MSMEs). The focus of this activity is the UMKM Semen Tape Bu Suwarti, a tape producer in Semen Hamlet, Musir Kidul Village. This MSME assistance work program is carried out using several methods including surveys, observations, interviews and discussions, as well as mentoring. The stages in this activity begin with socialization regarding the importance of NIB ownership for business legality and assistance in making NIB. The existence of NIB can help to increase transparency in the business world by making it easier for the government to monitor and enforce laws related to business licensing and regulations. In this way, NIB not only simplifies the business process, but is also an important step in supporting the growth of MSMEs as a sector of the Indonesian economy.